Does Mixed-Ownership Reform Affect Private Firms’ ESG Practices? Evidence from a Quasi-Natural Experiment in China - Cao, June; Li, W.; Xiao, S. (Wiley-Blackwell, 2022)
This study investigates the impact of property rights reform on private firms’ environmental, social, and governance (ESG) practices. ESG investing has become mainstream and a hot topic globally, but it is a black box of corporate ESG practices and performance. Importantly, it is not clear how to specifically enhance private firms’ ESG practices. This study addresses this problem by exploring an ideal setting of China's mixed-ownership reform in which private firms acquire equity in state-owned enterprises (SOEs). We examine whether and how this reform affects private acquirer firms’ ESG practices. Using a powerful difference-in-differences design, we find that mixed-ownership reform significantly enhances private firms’ ESG practices through heightened public scrutiny and the privileges of formal financing and government subsidies that are available due to the firms’ partial government ownership after mixed-ownership reform. Our findings have policy implications for promoting ESG practices and SOE reform. Specifically, our empirical evidence indicates that mixed-ownership reform can facilitate sustainable development for both SOEs and private firms.